Case Report: Heterotopic pregnancy after adenomyosis surgery: a rare case highlighting diagnostic pitfalls and clinical insights - Zhu, Qingqing; Cao, Shun; Wang, Qi; Xu, Jing; Hu, Hongjie (Frontiers in Medicine, 2025)
We present an extremely rare heterotopic pregnancy (HP) in a 33-year-old patient with multiple adenomyosis surgeries and bilateral salpingectomy, who conceived via assisted reproductive technology (ART). According to a review of the literature spanning two decades, concurrent intrauterine and extrauterine pregnancies are uncommon, especially in the case of intramural ectopic gestations. On day 31 post-embryo transfer, only an intrauterine pregnancy (IUP) was observed by ultrasound. However, early vaginal bleeding and high-risk factors prompted further ultrasound, revealing an intramural ectopic pregnancy. Though MRI initially misdiagnosed the lesion, reevaluation led to the correct diagnosis. Surgical removal of the ectopic pregnancy was performed while preserving the IUP, which progressed uneventfully. In the late second trimester, follow-up MRI confirmed an intact posterior uterine myometrium, ruling out uterine rupture and resolving lingering concerns. This case illustrates a progression from incomplete ultrasound assessment to an initial misinterpretation of MRI. Ultimately, complementary imaging was vital for accurately diagnosing and managing the intramural ectopic pregnancy, while safeguarding the intrauterine pregnancy by confirming uterine wall integrity later on. Highlighting the complexity of HP in a patient with adenomyosis conceived via ART, it underscores the importance of multiple imaging techniques for early diagnosis and ongoing monitoring in high-risk scenarios. These findings guide clinical strategies and emphasize the critical role of accurate imaging in protecting both maternal and fetal wellbeing.